PHYTOCHEMICAL AND PHARMACOLOGICAL EXAMINATION OF ENTANDROPHRAGMA ANGOLENSE AND CRYPTOLEPIS SANGUINOLENTA (1994)
Dried, pulverized stem bark and the root bark of Entandrophragma anqolense were separately extracted with methanol. The crude methanolic extract of the stem and root bark of E. anqolense were subjected to column fractionation and purification. This exercise afforded the Isolation of methyl angolensate, 2.26% yield from the stem bark and 0.27% yield from the root bark. The effect of the crude methanolic stem bark extract was investigated on indomethacin-induced gastric ulcer in rats. Its effect was dose-dependent, doses ranging from 0.4 to 1.6 gkg-1 body weight (BW) produced significant effect (P < 0.05). At the highest dose used (1.6gkg-1 BW), complete inhibition of ulceration occurred. Toxicity study showed that the extract was not toxic when doses ranging from 20-200gkg-1 BW was administered to experimental rats. It was established that methyl angolensate is the major anti- ulcer principle present in the methanolic extract of the stem bark of E. angolensate. Methyl angolensate produced a dose-related inhibition of gastric ulceration induced by indomethacin, 40mgkg BW being more effective than 40mgkg-1 BW of propanolol. 80mgkg-1 BW of methyl angolensate completely inhibited gastric ulceration. Methyl angolensate also significantly reduced gastric acid secretion induced by histamine and carbachol (1.0mgkg-1 BW). Thus we confirmed that methyl angolensate produces its anti-ulcer activity through inhibition of gastric acid secretion. The roots of Cryptolepis sanquinolenta were extracted with methanol. Column fractionation of the methanolic extract afforded the Isolation of a new benzocarboline alkaloid labelled (CS-1) melting point 272-274°C. Spectroscopic analysis of CS-1 including the infra-red (IR), 13 ultra-violet (UV), mass spectrum (MS), proton and C-nuclear magnetic spectroscopy were reported. This new alkaloid exhibited anti-microbial activity on five pathogenic organisms. The in-vivo anti-malarial study of the aqueous extract of the roots of sanguinolenta was done on Plasmodium yoeli nigeriensis in mice. Anti-malarial activity of the extract was determined by examining the blood schizontocidal action in established infection using chloroquine as Standard drug for comparison. The extract showed a dose-dependent effect against the malarial parasite.